2020
DOI: 10.3390/agronomy10121903
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Types of Biochar Mixed with Mineral Fertilization on the Development and Ionome of Winter Wheat (Triticum aestivum L.) Seedlings and Soil Properties in a Pot Experiment

Abstract: This paper focuses on the agronomic evaluation of a synthetic NPK (N in the form of urea, P and K in the form of phosphate monopotassium) fertilizers blended with four types of pine (Pinus sylvestris L.) wood biochar prepared at different thermal regimes (300 °C, 400 °C, 600 °C and 700 °C). The evaluation of benefits was done based on crop nutritional status and soil fertility. The pot experiment was set up with fertile Haplic Luvisol fertilized with 1.85 g kg−1 of blends of biochar (1.25 g) with urea (310 mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
1
11
0
1
Order By: Relevance
“…It is well-known that application of organic matters to soil led to increase its fertility (Kulczycki et al, 2020). In order to evaluate the benefit of biochar amendments to uptake of nutrients in tomato plants, the nutritional status of tomato plants grown in soil amended with different rates of biochar was assayed in both healthy and ToMV-infected plants.…”
Section: Effect Of Biochar On the Growth Of Tomato Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that application of organic matters to soil led to increase its fertility (Kulczycki et al, 2020). In order to evaluate the benefit of biochar amendments to uptake of nutrients in tomato plants, the nutritional status of tomato plants grown in soil amended with different rates of biochar was assayed in both healthy and ToMV-infected plants.…”
Section: Effect Of Biochar On the Growth Of Tomato Plantsmentioning
confidence: 99%
“…The dynamics of soil potassium was enhanced through biochar amendments which facilitate K uptake by plants (Wang et al, 2018). In another study, it was suggested that application of biochar at low doses with the synthetic fertilizers can improve plant yield and soil fertility (Kulczycki et al, 2020). Application of biochar may reduce Na uptake by plants which allow for survival and growth under salinity conditions (Farhangi-Abriz and Torabian, 2018).…”
Section: Effect Of Biochar On the Growth Of Tomato Plantsmentioning
confidence: 99%
“…The level of Mn in biochar is influenced by particle size, however it can be high [ 29 ]. The authors of [ 30 ] reported that the blend of ( Pinus sylvestris L.) wood biochar with nitrogen, phosphorus, and potassium (NPK) fertilizers increased the content of Mn and Fe in plants but decreased the contents of Ca and Mg.…”
Section: Resultsmentioning
confidence: 99%
“…con biochar y biofertilizantes. En relación a lo anterior, varios autores han reportado sinergias positivas entre biochar y consorcios microbianos con fertilizantes minerales (Bargaz et al, 2018;Dietrich et al, 2020;Kulczycki et al, 2020;Shi et al, 2020;Fitriatin et al, 2021).…”
Section: Resultados Y Discusiónunclassified